Case report: Oral anticoagulant combined with percutaneous coronary intervention for peripheral embolization of left ventricular thrombus caused by myocardial infarction in a patient with diabetes mellitus - Zhu, Chao; Zhou, Li; Gao, Hongli; Wang, Jiali; Li, Jiayu; Chen, Hui; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Left ventricular thrombus (LVT) is a well-recognized complication of myocardial infarction (MI) in patients with diabetes. An embolic complication caused by LVT is a key clinical problem and is associated with worsened long-term survival. Case presentation: A 45-year-old male with persistent left abdominal pain for one week and left leg fatigability was admitted to the emergency department. The cause of abdominal pain was embolism of the renal artery, splenic artery and superior mesenteric artery caused by cardiogenic thrombosis, which further led to splenic infarction and renal infarction. It was unclear when the MI occurred because the patient had no typical critical chest pain, which may have been related to diabetic complications, such as diabetic peripheral neuropathy. Diabetes played a pivotal role in the MI and LVT formation. Because coronary angiography suggested triple vessel disease, percutaneous transluminal coronary angioplasty (PTCA) was conducted, and two drug eluting stents were placed in the left anterior descending coronary artery (LAD). Due to a lack of randomized clinical control trials, the therapy of LVT and associated embolization has been actively debated. According to the present guidelines, this patient was treated with low–molecular weight heparin and warfarin (oral anticoagulant) for three months in addition to aspirin (100 mg/day) and clopidogrel (75 mg/day) for one year. No serious bleeding complications were noted, and follow-up examination showed no thrombus in the left ventricle or further peripheral thrombus events. Conclusion: Peripheral embolization of LVT caused by MI leading to multiple organ embolization remains a rare occurrence. Diabetes plays a pivotal role in MI and LVT formation. Successful revascularization of the infarct-related coronary artery and anticoagulation therapy are important to minimize myocardial damage and prevent LVT. The present case will help clinicians to recognize and manage LVT in patients with diabetes and related peripheral arterial thrombus events with anticoagulation.